Clinical and functional characterization of a novel RASopathy‐causing SHOC2 mutation associated with prenatal‐onset hypertrophic cardiomyopathy. Issue 8 (6th May 2019) - Motta, Marialetizia; Giancotti, Antonella; Mastromoro, Gioia; Chandramouli, Balasubramanian; Pinna, Valentina; Pantaleoni, Francesca; Di Giosaffatte, Niccolò; Petrini, Stefania; Mazza, Tommaso; D'Ambrosio, Valentina; Versacci, Paolo; Ventriglia, Flavia; et al.
Abstract: SHOC2 is a scaffold protein mediating RAS‐promoted activation of mitogen‐activated protein kinase (MAPK) signaling in response to extracellular stimuli. A recurrent activating mutation in SHOC2 (p.Ser2Gly) causes Mazzanti syndrome, a RASopathy characterized by features resembling Noonan syndrome and distinctive ectodermal abnormalities. A second mutation (p.Met173Ile) supposed to cause loss‐of‐function was more recently identified in two individuals with milder phenotypes. Here, we report on the third RASopathy‐causing SHOC2 mutation (c.807_808delinsTT, p.Gln269_His270delinsHisTyr), which was found associated with prenatal‐onset hypertrophic cardiomyopathy. Structural analyses indicated a possible impact of the mutation on the relative orientation of the two SHOC2's leucine‐rich repeat domains. Functional studies provided evidence of its activating role, revealing enhanced binding of the mutant protein to MRAS and PPP1CB, and increased signaling through the MAPK cascade. Differing from SHOC2 S2G, SHOC2 Q269_H270delinsHY is not constitutively targeted to the plasma membrane. These data document that diverse mechanisms in SHOC2 functional dysregulation converge toward MAPK signaling upregulation. Abstract : SHOC2 positively modulates RAS‐mitogen‐activated protein kinase (MAPK) signaling and a recurrent activating mutation constitutively targeting SHOC2 to the plasma membrane causes virtually all cases of Mazzanti syndrome, a RASopathy resembling Noonan syndrome but characterized by distinctive ectodermal features. We report on a novel RASopathy‐causing SHOC2 mutation, which does not result in constitutive targeting of SHOC2 to the plasma membrane but enhances SHOC2 binding to MRAS and PPP1CB and boosts activation of the MAPK pathway. These data document that diverse mechanisms in SHOC2 functional dysregulation converge toward MAPK signaling upregulation.